Investigating the Relationship between Work-Family Conflict and Job Stress with Emotional Exhaustion with Mediation of Personnel Capabilities in Male and Female Employees of The Islamic Republic of Iran Airlines (HOMA) - Masoudi Hemmatabadi, Fatemeh; Haji Hosseini Mesgar, Mahsa; Azadyekta, Mehrnaz; Nasrollahi, Bita (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the relationship between work-family conflict and job stress with emotional fatigue mediated by personnel capabilities in employees of the Commercial Unit of the Islamic Republic of Iran Airlines (Homa). Method: The present study is a correlational study. In order to achieve the goal, from a population of 864 employees, 265 people were selected by simple random sampling method and Completed the Work-Conflict Questionnaire by Carlson et al. (2000), job stress by Hellerigel and Slocom (2000), Maslash burnout (1981) and the character skills of Seligman and Peterson (2004). The obtained data were analyzed using Pearson correlation, multiple regression analysis, bootstrap and path analysis using SPSS22 software. Results: The results showed that work-family conflict and job stress were related to emotional fatigue due to secretory abilities and this relationship was directly and indirectly significant. There is a significant positive relationship between work-family conflict with emotional fatigue, a significant positive relationship between job stress and emotional fatigue, a significant positive relationship between work-family conflict and job stress and personnel capabilities, a significant positive relationship between job stress and secretarial ability with emotional fatigue, there was a significant negative relationship between secretory abilities and emotional fatigue (P<0.05). Conclusion: Considering the significant and negative relationship between personnel capabilities and emotional fatigue and work-family conflict, it is necessary to provide a suitable background for employees to get acquainted with the scientific management of work-family conflict and training and promotion of this variable in employees by organizations.